PENGEMBANGAN E-MODUL BERBASIS FLIP PDF CORPORATE EDITION PADA TEMA 7 SUBTEMA 1 PEMBELAJARAN 1 KELAS V SDN 39 PONTIANAK KOTA - Muhammad Ridho Hakiki; Dyoty Auliya Vilda Ghasya; Siti Halidjah (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2024)
This research generally has the aim of producing an E-Module based on Flip PDF Corporate Edition media for 5th grade elementary school students valid and practically to be used in assisting thematic learning activities, theme 7 sub-theme 1 learning 1. The method used in this study is Brog and Gall's method. The data sources in this study were a homeroom teacher, 33 students, fifth grade of B class of SDN 39 Pontianak Kota and 2 expert validators, namely design and material experts. The results showed that the development of E-Modules based on Flip PDF Corporate Edition has passed seven stages of research, including: determining potential and problems, collecting data, making product designs, conducting design validation, revising design parts, carrying out product trials, and revising product parts. The practicality of E-Module development products based on Flip PDF Corporate Edition has a category of "Very Practical" from student practitioners, namely in the aspect of practicality, small groups obtained an average score of 4.72 with the category "Very Practical" and large groups obtained an average score of 4.40 with the category "Very Practical".